Cultivating social relationships and disrupting social isolation in low‐income, high‐disparity neighbourhoods in Ohio, USA. (9th February 2021) - Parsons, Allison A.; Leggett, Dawna; Vollmer, Daniela; Perez, Valerie; Smith, Rachel; Goodman, Emily; Mayes, Crystal; McLellan, Chellie; Laird, Nancy; Beck, Andrew F.; Kahn, Robert; Riley, Carley
Abstract: Social isolation undermines health. Inequities in social networks exist due to historical and contemporary practices of socioeconomic and racial segregation. Thus, lower income and minority families are less likely to have the number, strength, and variety of social connections as higher income and white families. Therefore, social isolation may contribute to inequities in health and well‐being across socioeconomic and racial groups. Disrupting social isolation by strengthening social networks may be a meaningful way to equitably improve population health. In this study we aimed to better understand the factors that influence the formation and sustainment of social connections in neighbourhoods experiencing a disproportionate burden of social needs and poor health outcomes. Participants were recruited through our community–academic partnership, Healthy Homes (HH). Healthy Homes serves families with pregnant women and/or children <6 years in two low‐income, high‐morbidity neighbourhoods, focusing on supporting families' needs and hopes. Between October 2016 and April 2017, we conducted in‐depth qualitative interviews ( n = 20) with English‐speaking mothers and grandmothers of children under <6 years. Interviews were audio‐recorded, transcribed verbatim and independently coded. After applying an a priori code list, we conducted emergent coding to identify additional themes. Themes focused on the social environment, including social connections and social isolation, among vulnerable populations in included neighbourhoods. Families want connection to one another and to resources but look to others to facilitate those connections. Families may want or need social connections but do not engage if it means sacrificing their values or sense of self‐worth. These findings provide a deeper understanding of the factors that might allow us to disrupt social isolation by building relationships in communities that face social and health inequities.